A method and application of isotropic shrinkage of three-dimensional micro-nanostructures

In the manufacturing process of inorganic 3D micro-nano structures, the target structure is formed using polymer film and etching technology and pyrolytic calcination is solved, and the morphological distortion problem caused by pyrolytic shrinkage is achieved, and the high morphological quality and Manufacturing of 3D micro-nano structures without distortion.

CN118561530BActive Publication Date: 2025-02-07HUAZHONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410699513.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-02-07
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

Inorganic 3D micro-nano structures are prone to morphological distortion due to substrate adhesion during the thermal decondensation process, which limits its stable preparation and large-scale application.

Method used

By mixing the polymer material with a solvent and spin-coating it on the substrate, etching part of the substrate surface to expose the substrate, forming a target three-dimensional three-dimensional structure, and performing stiffness strengthening and pyrolytic calcining, it can achieve Three-dimensional micro-nano structure with isotropic shrinkage.

Benefits of technology

It effectively solves the problem of morphological distortion caused by pyrolysis shrinkage, and achieves high morphological quality, distortion-free and stable in-situ manufacturing of 3D micro-nano structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118561530B_ABST
    Figure CN118561530B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of micro-nano processing technology, and more specifically, it relates to an isotropic shrinkage method and application of a three-dimensional micro-nano structure. The present application prepares a polymer film by mixing a polymer material and a solvent and then spin-coating it on the surface of a substrate, then etches the polymer film to expose part of the substrate surface, and uses the etched area as the starting processing position to process the raw material of the three-dimensional structure into a target three-dimensional structure, and then performs a stiffness strengthening treatment, soaks the above-mentioned solvent, and pyrolyzes and calcines the above-mentioned target three-dimensional structure to obtain an isotropically shrinkable three-dimensional micro-nano structure. The isotropic shrinkage method of the three-dimensional micro-nano structure provided in the present application can effectively solve the problems of morphological distortion and poor stability caused by pyrolysis and shrinkage of the 3D micro-nano structure during the preparation process, and at the same time realizes the simplified and stabilized in-situ preparation of the 3D micro-nano structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of micro-nano processing technology, and more specifically, relates to an isotropic shrinkage method and application of a three-dimensional micro-nano structure. Background Art

[0002] Three-dimensional (3D) micro-nanostructures refer to functional materials or structures with complex 3D morphology at the micro-nanoscale. They not only have novel physical properties such as quantum effects, size effects and surface effects given by nanomaterials and structures, but also can achieve coordinated modulation of physical properties such as spin polarization, exciton behavior, electron transport and coupling, and wavefront regulation through 3D geometric structures. Therefore, 3D micro-nanostructures have become the focus of current research on the application of micro-nanotechnology. For example, 3D micro-nanostructures have a larger specific surface area than traditional two-dimensional structures, which can significantly improve the sensitivity of metal oxide microsensors and the energy density of energy storage devices; the localized surface plasmon resonance effect of 3D metal nanostructures can be used to enhance optical signals, thereby improving photocatalytic efficiency and optical detection sensitivity; 3D zinc oxide micro-nanostructures can be used to prepare vascular stents, medical endoscopes, etc., and are expected to serve in the fields of medical detection and tissue repair; 3D metal nanoarray structures have been successfully applied to the development of flexible electronic devices and 3D integrated microsystems, providing a reliable technical foundation for the research and development of civilian electronic products such as flexible electronic skin and wearable devices.

[0003] At present, inorganic 3D micro-nano structures are generally formed by 3D printing an organic-inorganic mixture on a substrate, and then the organic components are decomposed at high temperature by an annealing process to obtain the 3D micro-nano structure. However, during the annealing process, the 3D micro-nano structure adheres to the substrate, and the detachment of the organic components will cause the 3D micro-nano structure to shrink by 30% to 80%, which will cause serious morphological distortion, limiting the stable preparation and large-scale application of inorganic 3D micro-nano structures. Therefore, the problem of morphological shrinkage and distortion has become a key challenge in the processing, manufacturing and application development of 3D micro-nano structures.

[0004] At present, the technical routes to solve the problem of morphological shrinkage distortion of 3D micro-nano structures during pyrolysis and shrinkage mainly include the following two solutions: 1) designing a buffer base, spring or support column at the bottom of the 3D micro-nano structure to reduce the contact area between the 3D micro-nano structure and the substrate, thereby slowing down the shrinkage distortion; 2) transferring the 3D micro-nano structure to a smooth substrate after peeling it off for pyrolysis to reduce the contact force between the structure and the substrate, thereby slowing down the shrinkage distortion. For example, the Julia research group in the United States (Adv. Mater. 2019, 31, e1901345) and Jingwei Liu et al. from Huazhong University of Science and Technology (Adv. Mater. Technol. 2021, 7, 2101230) designed a 3D micro-nanostructure with a base to alleviate the morphological distortion caused by pyrolysis shrinkage; Andrey Vyatskikh et al. from the California Institute of Technology designed a buffer spring at the bottom of the 3D structure (Nano Lett., 2020, 20, (5), 3513-3520) in the hope that the spring would serve as a shrinkage buffer layer during the pyrolysis process to reduce the deformation of the 3D structure. These methods have alleviated the morphological distortion caused by pyrolysis shrinkage to a certain extent, but have not achieved better results. Tomohiro Mori and others from the Singapore University of Technology and Design proposed a solution in which 3D micro-nano structures are peeled off and then transferred to a smooth substrate for thermal decomposition (Nat. Commun. 2023, 14, 5876). The 3D micro-nano structure is transferred to a smooth substrate through a microneedle to reduce the adhesion between the 3D structure and the substrate, thereby effectively reducing the morphological distortion caused by structural shrinkage. However, this also brings about a series of parasitic problems such as time-consuming and cumbersome microneedle transfer steps, inability to prepare in situ on a large scale, and easy detachment of the structure.

[0005] Therefore, there is currently a lack of a method in the world that can completely solve the morphological distortion of 3D micro-nano structures produced during thermal decomposition and shrinkage, making it difficult to achieve distortion-free, large-scale in-situ manufacturing of inorganic 3D micro-nano structures. Summary of the invention

[0006] In view of the defects of the prior art, the purpose of this application is to provide an isotropic shrinkage method and application of three-dimensional micro-nano structures, aiming to solve the problem of morphological distortion caused by pyrolysis shrinkage of inorganic 3D micro-nano structures during the manufacturing process, and to achieve high morphological quality, distortion-free and stable in-situ manufacturing of 3D micro-nano structures.

[0007] To achieve the above objectives, the present application provides an isotropic shrinkage method for a three-dimensional micro-nano structure, comprising the following steps:

[0008] S1, spin coating a polymer solution on a substrate, and then heat-baking to obtain a polymer film; the polymer solution is formed by uniformly mixing a polymer material and a solvent, and the polymer material is one or more organic polymers with a molecular weight ≥ 1000;

[0009] S2, etching the polymer film to expose a portion of the substrate surface, taking the etched region as the starting processing position, processing the raw material of the three-dimensional structure into a target three-dimensional structure, so that the target three-dimensional structure is located at the bottom of the etched region and contacts the substrate surface, while the bottom of other parts contacts the unetched polymer film surface, wherein the area ratio of the etched region to the bottom of the target three-dimensional structure is 1:(2-100);

[0010] The polymer film and the raw materials of the three-dimensional structure have different polarities, making them insoluble;

[0011] S3, performing a stiffness strengthening treatment on the target three-dimensional structure, and then immersing it in the solvent to dissolve the unetched polymer film to obtain a three-dimensional micro-nano polymer structure;

[0012] S4. Pyrolyze and calcine the three-dimensional micro-nano polymer structure to obtain an isotropically shrunk three-dimensional micro-nano structure.

[0013] Preferably, in step S1, the polymer material is selected from at least one of polyethylene glycol, polypropylene glycol, polybutylene glycol, polyvinyl chloride, polystyrene, polyisobutylene, polyvinyl alcohol, polypropylene alcohol, polychloroprene, vinylidene chloride-vinyl chloride copolymer, vinylidene chloride-vinyl chloride copolymer, polychloroprene and polybutadiene.

[0014] Preferably, in step S1, the above-mentioned solvent is used to dissolve the above-mentioned polymer material to prepare a polymer solution, including but not limited to at least one of aromatic hydrocarbon organic solvents, aliphatic hydrocarbon organic solvents, chlorinated hydrocarbon organic solvents, ketone organic solvents, alcohol organic solvents, benzene organic solvents, tetrahydrofuran, carbon tetrachloride, deionized water and dimethyl sulfoxide.

[0015] Preferably, in step S1, the mass ratio of the polymer material to the solvent is (0.01-0.5):1.

[0016] Further preferably, in step S1, the mass ratio of the polymer material to the solvent is (0.05-0.1):1.

[0017] Preferably, in step S1, the substrate is selected from at least one of soda-lime glass, a silicon wafer and a silicon dioxide wafer.

[0018] Preferably, in step S1, the heat-baking temperature is 50°C to 150°C, and the heat-baking time is 30s to 300s.

[0019] Preferably, in step S2, the etching is selected from at least one of laser etching, mask etching, plasma etching and mechanical etching.

[0020] Preferably, in step S2, the area ratio of the etching region to the bottom of the target three-dimensional structure is 1:(10-50).

[0021] Preferably, in step S3, the stiffness strengthening treatment is performed by at least one of ultraviolet irradiation and thermal baking.

[0022] Further preferably, in step S3, the temperature of the stiffness strengthening treatment is 50° C. to 200° C., and the time is 2 h to 12 h.

[0023] Preferably, in step S3, the soaking time in the solvent is 1 hour to 6 hours.

[0024] Preferably, in step S4, the atmosphere of the pyrolysis calcination includes at least one of air, oxygen, hydrogen and argon, the temperature of the pyrolysis calcination is 400° C. to 1200° C., and the time of the pyrolysis calcination is 5 h to 16 h.

[0025] The present application provides an isotropically shrinkable three-dimensional micro-nano structure prepared according to the above method.

[0026] The present application also provides a product comprising the above-mentioned isotropically shrinkable three-dimensional micro-nano structure.

[0027] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:

[0028] (1) The present application provides a method for isotropic shrinkage of a three-dimensional micro-nano structure, which comprises the steps of mixing a polymer material and a solvent and then spin-coating the mixture on a substrate surface to prepare a polymer film, then etching the polymer film to expose a portion of the substrate surface, and processing the raw material of the three-dimensional structure into a target three-dimensional structure with the etching area as the starting processing position, and then subjecting the target three-dimensional structure to a stiffness strengthening treatment, soaking in the solvent, and pyrolysis and calcination to obtain an isotropically shrinkable three-dimensional micro-nano structure. The present application utilizes a polymer film as a sacrificial layer, so that the prepared 3D micro-nano structure is located at the bottom of the etching area and contacts the substrate surface, while the bottom of other parts can be suspended from the substrate, thereby solving the morphological distortion of the 3D micro-nano structure caused by the adhesion of the substrate during the pyrolysis and shrinkage process, and effectively eradicating the morphological distortion problem of the current inorganic 3D micro-nano structure during the manufacturing process. In addition, the method provided in this application also realizes the simplified and stabilized in-situ preparation of 3D micro-nano structures, which is suitable for the integrated in-situ manufacturing of 3D micro-nano functional structures in the fields of micro-nano optics, electronics, biomedicine, high-precision sensing, energy storage, etc., and provides reliable technical support for the processing, manufacturing and application development of 3D micro-nano structures.

[0029] (2) The solvents or monomers contained in the existing three-dimensional structure raw materials are usually weak polar solvents such as acrylates and epoxy resins, or strong polar solvents such as benzene, alcohols, ethers, and organic acids. Based on the principle of like dissolves like, the present application can adaptively use strong polar, weak polar or non-polar polymer films for various three-dimensional structure raw materials on the market, so that the polarity of the polymer film is lower or higher than the three-dimensional structure raw material, thereby ensuring that the polymer film will not be dissolved by the three-dimensional structure raw material. The present application uses the etching area as the starting processing position, and processes various three-dimensional structure raw materials such as organic-inorganic mixtures and precursor resins currently on the market into target three-dimensional structures, which can achieve distortion-free manufacturing of various inorganic 3D micro-nano structures.

[0030] (3) The isotropic shrinkage method of the three-dimensional micro-nano structure provided in this application uses inexpensive, easily available materials, which can achieve the manufacturing of 3D micro-nano functional structures at a lower cost, and is of great significance to the industrial development of 3D micro-nano devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a flow chart of an isotropic shrinkage method of a three-dimensional micro-nano structure provided by the present application;

[0032] Figure 2 is an etched image of a polymer film provided by the present application;

[0033] Figure 3It is an image of the 3D micro-nanostructure of the zinc ion polymer after solvent cleaning provided in Example 1 of the present application, wherein content a is a Primitive 3D structure, content b is a partial enlarged view of the Primitive 3D structure, content c is a Diamond3D structure, and content d is a partial enlarged view of the Diamond 3D structure;

[0034] Figure 4 The image of the isotropically shrunk zinc oxide 3D micro-nano structure after pyrolysis and calcination provided in Example 1 of the present application, wherein content a is a Primitive 3D structure, content b is a partial enlarged view of the Primitive 3D structure, content c is a Diamond 3D structure, and content d is a partial enlarged view of the Diamond 3D structure;

[0035] Figure 5 The image of the zinc ion polymer 3D micro-nano structure provided in Comparative Example 1 of the present application, wherein content a is a Primitive 3D structure, content b is a partial enlarged view of the Primitive 3D structure, content c is a Diamond 3D structure, and content d is a partial enlarged view of the Diamond 3D structure;

[0036] Figure 6 This is an image of the zinc oxide 3D micro-nano structure after pyrolysis and calcination provided in Comparative Example 1 of the present application, wherein content a is a Primitive 3D structure, content b is a partial enlarged view of the Primitive 3D structure, content c is a Diamond 3D structure, and content d is a partial enlarged view of the Diamond 3D structure. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0038] The present application provides an isotropic shrinkage method for a three-dimensional micro-nanostructure, see Figure 1 , including the following steps:

[0039] S1, spin coating a polymer solution on a substrate, and then heat-baking to obtain a polymer film; the polymer solution is formed by uniformly mixing a polymer material and a solvent, and the polymer material is one or more organic polymers with a molecular weight ≥ 1000;

[0040] S2, etching the polymer film to expose a portion of the substrate surface, taking the etched area as the starting processing position, processing the raw material of the three-dimensional structure into a target three-dimensional structure, so that the target three-dimensional structure is located at the bottom of the etched area and contacts the substrate surface, while the bottom of other parts contacts the unetched polymer film surface, wherein the area ratio of the etched area to the bottom of the target three-dimensional structure is 1:(2-100);

[0041] The polymer film and the raw materials of the three-dimensional structure have different polarities, making them insoluble;

[0042] S3, performing a stiffness strengthening treatment on the target three-dimensional structure, and then immersing it in the above-mentioned solvent to dissolve the unetched polymer film to obtain a three-dimensional micro-nano polymer structure;

[0043] S4. Pyrolysis and calcination are performed on the three-dimensional micro-nano polymer structure to obtain an isotropically shrunk three-dimensional micro-nano structure.

[0044] In some embodiments, in step S1, the polymer material is selected from at least one of organic polymers with a molecular weight of 1000 to 400000. In a preferred embodiment, the polymer material is selected from at least one of polyethylene glycol, polypropylene glycol, polybutylene glycol, polyvinyl chloride, polystyrene, polyisobutylene, polyvinyl alcohol, polypropylene alcohol, polychloroprene, vinylidene chloride-vinyl chloride copolymer, vinylidene chloride-vinyl chloride copolymer, polychloroprene, and polybutadiene.

[0045] In step S1 of the present application, the above-mentioned solvent is used to dissolve the above-mentioned polymer material and then prepare a polymer solution. It should be understood that the present application does not specifically limit the type of solvent, as long as it can dissolve the above-mentioned polymer material. In some embodiments, the above-mentioned solvent includes but is not limited to at least one of aromatic hydrocarbon organic solvents, aliphatic hydrocarbon organic solvents, chlorinated hydrocarbon organic solvents, ketone organic solvents, alcohol organic solvents, benzene organic solvents, tetrahydrofuran, carbon tetrachloride, deionized water and dimethyl sulfoxide.

[0046] In some embodiments, in step S1, the mass ratio of the polymer material to the solvent is (0.01-0.5):1, preferably (0.05-0.1):1.

[0047] The present application does not limit the method of "mixing" in step S1, as long as the polymer material and the solvent can be mixed evenly, such as but not limited to ultrasonic mixing and stirring mixing. In some embodiments, in step S1, the stirring and mixing time is not less than 2 hours, preferably 2 hours to 10 hours. It is understandable that those skilled in the art can adaptably extend or shorten the mixing time according to different mixing methods, which is also within the scope of protection of the present application.

[0048] In some embodiments, in step S1, the substrate is selected from any one of soda-lime glass, silicon wafer and silicon dioxide wafer. The present application does not limit the type and thickness of the substrate, and the appropriate type and thickness can be selected according to the experimental conditions, all within the protection scope of the present application. In order to facilitate laser focusing, in some embodiments, the thickness of the substrate is 0.2 mm to 1 mm, preferably 0.3 mm.

[0049] In some embodiments, in step S1, the spin coating parameters are pre-spin coating at a rotation speed of 100 rps to 750 rps for 5 s to 20 s, and then spin coating at a rotation speed of 750 rps to 5000 rps for at least 60 s. First, spin coating at a low speed allows the polymer solution to be evenly spread on the substrate, and then spin coating at a high speed allows the polymer solution to form a thin film on the substrate.

[0050] In some embodiments, in step S1, the above-mentioned heat baking temperature is 50°C to 150°C, and the heat baking time is 30s to 300s. It should be understood that those skilled in the art can adaptively increase or decrease the heat baking temperature, extend or shorten the heat baking time according to the heat baking treatment method, which is also within the protection scope of this application.

[0051] The present application does not limit the thickness of the polymer film. Those skilled in the art can select a suitable thickness of the polymer film according to actual needs, which is within the protection scope of the present application. In some embodiments, the thickness of the polymer film is 0.2 μm to 10 μm.

[0052] In some embodiments, in step S2, the etching includes but is not limited to at least one of laser etching, mask etching, plasma etching and mechanical etching.

[0053] It should be understood that the present application does not limit the type of raw materials for the above-mentioned three-dimensional structure. Any type of three-dimensional structure raw materials reported in the prior art can be used, which can be an organic-inorganic mixture, or a precursor resin such as a metal ion photosensitive resin, a quantum dot resin, or a metal nanoparticle photosensitive resin. The present application does not limit the source of the above-mentioned three-dimensional structure raw materials. It can be configured by the laboratory itself or purchased from commercially available products. The present application has no special restrictions on the solvent or monomer used to prepare the three-dimensional structure raw materials. It can be a weak polar solvent such as acrylate, epoxy resin, or a strong polar solvent such as benzene, alcohol, ether, organic acid. In some embodiments, the raw materials of the above-mentioned target three-dimensional structure are selected from the metal ion photosensitive resin material (precursor resin) prepared by the patent document CN112947002A and the metal ion gel composite (organic-inorganic mixture) prepared by the document (Nanomicro Lett, 2023, 15 (1): 180.).

[0054] In some embodiments, the above-mentioned polymer film and the raw materials of the above-mentioned three-dimensional structure have different polarities, making the polymer film and the raw materials of the three-dimensional structure immiscible, so that when the raw materials of the three-dimensional structure are processed into the target three-dimensional structure with the above-mentioned etching area as the starting processing position, the unetched polymer film can contact a partial area of ​​the bottom of the target three-dimensional structure without being dissolved by the raw materials of the three-dimensional structure.

[0055] In some embodiments, in step S2, the area ratio of the etching area and the bottom of the target three-dimensional structure is 1:(2-100), preferably 1:(10-50), so that only a small area (etching area) of the bottom of the obtained target three-dimensional structure is in contact with the substrate, and other areas of the bottom of the target three-dimensional structure are in contact with the polymer film.

[0056] The present application does not limit the above method of processing the raw material of the three-dimensional structure into the target three-dimensional structure with the etching area as the center. Those skilled in the art can use any technology well known in the art to process the raw material of the three-dimensional structure into the target three-dimensional structure with the etching area as the starting processing position. No matter what technology is used, it is within the protection scope of the present application. For example, but not limited to inkjet printing, aerosol printing, femtosecond laser direct writing, stereolithography.

[0057] In some embodiments, in step S3, the stiffness enhancement treatment includes but is not limited to at least one of ultraviolet irradiation and thermal baking, the purpose of which is to enhance the stiffness of the target three-dimensional structure, so that after the target three-dimensional structure is immersed in the solvent to dissolve the unetched polymer film, the target three-dimensional structure is located at the bottom of the etched area and contacts the substrate surface, while the bottom of other parts can be suspended on the substrate. The inventor of the present application has found through experiments that if the target three-dimensional structure is directly immersed in the solvent without stiffness enhancement treatment, when the unetched polymer film is dissolved, the strength of the target three-dimensional structure is too weak, and structural deformation and the like are prone to occur.

[0058] In some embodiments, the above-mentioned target three-dimensional structure is subjected to stiffness strengthening treatment by heat baking. In some embodiments of the present application, the heat baking temperature is 50°C to 200°C, and the heat baking time is 2h to 12h. It should be understood that those skilled in the art can adaptively increase or decrease the heat baking temperature, extend or shorten the heat baking time according to the heat baking treatment method, which is also within the protection scope of the present application.

[0059] In some embodiments, in step S3, the time for soaking in the solvent is 1 hour to 6 hours, the purpose is to dissolve the unetched polymer film, so that only a small area (etched area) at the bottom of the three-dimensional micro-nano polymer structure is in contact with the substrate, and the other areas at the bottom of the three-dimensional micro-nano polymer structure can be suspended from the substrate. In a preferred embodiment, in step S3, the time for soaking in the solvent is 1 hour to 3 hours.

[0060] In some embodiments, in step S4, the pyrolysis calcination atmosphere includes at least one of oxygen, air, argon and hydrogen. In practical applications, those skilled in the art can select a suitable pyrolysis calcination atmosphere according to the raw materials of the three-dimensional structure.

[0061] In some embodiments, in step S4, the temperature of the pyrolysis calcination is 400° C. to 1200° C., and the time of the pyrolysis calcination is 5 h to 16 h.

[0062] The present application provides an isotropically shrinkable three-dimensional micro-nano structure prepared according to the above method. It can be understood that the isotropic shrinkage method of the three-dimensional micro-nano structure provided in the present application can prepare the isotropically shrinkable three-dimensional micro-nano structure, that is, the present application provides a method for preparing the isotropically shrinkable three-dimensional micro-nano structure.

[0063] Furthermore, the present application also provides the use of the above-mentioned isotropically shrinkable three-dimensional micro-nano structure in the preparation of three-dimensional micro-nano devices.

[0064] Based on this, the present application provides a product comprising the above-mentioned isotropically shrinkable three-dimensional micro-nano structure.

[0065] The above technical solutions are described in detail below in conjunction with specific embodiments. It should be understood that these are merely exemplary and are not intended to limit the present application. Materials identical or similar to the types, models, qualities, properties or functions of the following reagents and instruments can be used to implement the present application. The experimental methods used in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial sources.

[0066] The following are examples:

[0067] Example 1

[0068] Using polyvinyl chloride as a non-polar polymer material and cyclohexanone as a non-polar solvent, a femtosecond laser etching technique is used to etch a non-polar polymer film, and a weakly polar zinc ion photosensitive resin (the raw material preparation method is the same as that of patent document CN112947002A) is used to process a 3D micro-nano structure. The specific steps are as follows:

[0069] S1. Take 750 mg of polyvinyl chloride with a molecular weight of 77,000 and mix it with 10 g of cyclohexanone and stir it magnetically for 6 hours to obtain a colorless and transparent polyvinyl chloride solution. Fix the soda-lime glass substrate on the spin coater, take 300 μL of colorless and transparent polyvinyl chloride solution and evenly drop it on the substrate, then set the pre-spin coating parameters (speed of 500 rps, time of 10 s) and spin coating parameters (speed of 1500 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a 75°C hot plate for 80 seconds to obtain a soda-lime glass substrate with a 0.6 μm polyvinyl chloride film spin-coated.

[0070] S2, placing the soda-lime glass substrate with the polyvinyl chloride film spin-coated obtained in step S1 in a femtosecond laser etching system for pattern etching, with the etching parameters set to 10 mm / s, 50 mW, Figure 2 The polyvinyl chloride film is patterned and etched. Then a drop of zinc ion photosensitive resin is dropped on the etched area, and a femtosecond laser direct writing technique is used to process a 3D micro-nano polymer structure with the etched area as the center. The area ratio of the etched area to the bottom of the 3D micro-nano polymer structure is 1:40.

[0071] S3, the sample obtained in step S2 was placed in an oven at 80°C for 10 hours for stiffness strengthening treatment, and then the sample was taken out and immersed in cyclohexanone solvent for 2 hours. The 3D micro-nanostructure image of the zinc ion polymer after washing with cyclohexanone was shown in FIG. Figure 3 ,in Figure 3 Content a is a Primitive 3D structure. Figure 3 Content b is a partial enlarged view of the Primitive 3D structure. Figure 3 Content c is Diamond 3D structure, Figure 3 Content d is a partial enlarged image of the Diamond 3D structure. It can be seen that the bottom of the zinc ion polymer 3D micro-nano structure is in contact with the substrate only through the etched area, and the other areas of the bottom of the zinc ion polymer 3D micro-nano structure are suspended on the substrate.

[0072] S4, the sample obtained in step S3 was pyrolyzed and calcined at 600°C for 10 h in an oxygen atmosphere to obtain a zinc oxide 3D micro-nano structure ( Figure 4 ),in Figure 4 Content a is a Primitive 3D structure. Figure 4 Content b is a partial enlarged view of the Primitive 3D structure. Figure 4 Content c is Diamond 3D structure, Figure 4 Content d is a partial enlarged view of the Diamond 3D structure. Figure 3 , Figure 4It can be seen that after the pyrolysis treatment, the morphology of the zinc oxide 3D micro-nano structure prepared in Example 1 of the present application is not distorted, and has high 3D morphology quality.

[0073] Example 2

[0074] Using polyvinyl chloride as a non-polar polymer material and cyclohexanone as a non-polar solvent, a femtosecond laser etching technique is used to etch a non-polar polymer film, and a weakly polar cobalt ion photosensitive resin (the raw material preparation method is the same as that of patent document CN112947002A) is used to process a 3D micro-nano structure. The specific steps are as follows:

[0075] S1. Take 500 mg of polyvinyl chloride with a molecular weight of 95,000 and mix it with 10 g of cyclohexanone and stir it magnetically for 4 hours to obtain a colorless and transparent polyvinyl chloride solution. Fix the silicon dioxide substrate on the spin coater, then take 300 μL of colorless and transparent polyvinyl chloride solution and evenly drop it on the substrate, set the pre-spin coating parameters (speed of 500 rps, time of 10 s) and spin coating parameters (speed of 2000 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a 75°C hot plate for 60 seconds to obtain a silicon dioxide substrate with a 0.3 μm polyvinyl chloride film spin-coated.

[0076] S2. Place the silicon dioxide substrate with the polyvinyl chloride film spin-coated obtained in step S1 under a femtosecond laser etching system for pattern etching, and set the etching parameters to 10 mm / s, 50 mW. Then drop a drop of cobalt ion photosensitive resin on the above-mentioned etching area, and use femtosecond laser direct writing technology to process the 3D micro-nano polymer structure with the etching area as the center, and the area ratio of the etching area to the bottom of the 3D micro-nano polymer structure is 1:16.

[0077] S3. Place the sample obtained in step S2 in an oven at 80° C. for 10 hours for stiffness strengthening treatment, then take out the sample and immerse it in a cyclohexanone solvent for 1.5 hours.

[0078] S4. Pyrolyze and calcine the sample obtained in step S3 at 800° C. for 6 hours in an air atmosphere to obtain a distortion-free, high-quality cobalt oxide 3D micro-nano structure.

[0079] Example 3

[0080] Polyisobutylene is used as a non-polar polymer material, hexane is used as a non-polar solvent, a plasma etching technique is used to etch the non-polar polymer film, and a weakly polar zinc ion photosensitive resin (same as in Example 1) is used to process the 3D micro-nano structure. The specific steps are as follows:

[0081] S1. Take 1000 mg of polyisobutylene with a molecular weight of 3500 and mix it with 10 g of hexane and stir it magnetically for 6 hours to obtain a colorless and transparent polyisobutylene solution. Fix the soda-lime glass substrate on the spin coater, then take 300 μL of colorless and transparent polyisobutylene solution and drip it evenly on the substrate, set the pre-spin coating parameters (rotation speed of 500 rps, time of 10 s) and spin coating parameters (rotation speed of 1500 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a 60°C hot plate for 90 seconds to obtain a soda-lime glass substrate with a 2.2 μm polyisobutylene film spin-coated thereon.

[0082] S2, spin-coating AZ photoresist on the soda-lime glass substrate with polyisobutylene film obtained in step S1, patterning with a maskless photolithography machine, and then placing it in a plasma etching for etching, the etching atmosphere is argon, the chamber pressure is set to 50mT, and the frequency is set to 20MHz. Then drop a drop of zinc ion photosensitive resin on the above-mentioned etching area, and use femtosecond laser direct writing technology to process the 3D micro-nano polymer structure with the etching area as the center, and the area ratio of the etching area to the bottom of the 3D micro-nano polymer structure is 1:10.

[0083] S3. Place the sample obtained in step S2 in an oven at 80° C. for 10 hours for stiffness strengthening treatment, then take out the sample and immerse it in a hexane solvent for 2 hours.

[0084] S4. The sample obtained in step S3 is pyrolyzed and calcined at 600° C. for 10 h in an oxygen atmosphere to obtain a 3D zinc oxide micro-nanostructure with no distortion and high morphological quality.

[0085] Example 4

[0086] Using polyvinyl alcohol as a strong polar polymer material and deionized water as a strong polar solvent, a microneedle mechanical etching technique is used to pattern a strong polar polymer film, and a weakly polar cobalt ion photosensitive resin (same as Example 2) is used to process a 3D micro-nano structure. The specific steps are as follows:

[0087] S1. Take 500 mg of polyvinyl alcohol with a molecular weight of 300,000 and mix it with 10 g of deionized water and stir it magnetically for 3 hours to obtain a colorless and transparent polyvinyl alcohol solution. Fix the soda-lime glass substrate on the spin coater, take 300 μL of colorless and transparent polyvinyl alcohol solution and evenly drop it on the substrate, then set the pre-spin coating parameters (speed of 500 rps, time of 10 s) and spin coating parameters (speed of 2000 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a hot plate at 80°C for 90 seconds to obtain a soda-lime glass substrate with a 0.4 μm polyvinyl alcohol film spin-coated thereon.

[0088] S2. The soda-lime glass substrate spin-coated with a polyvinyl alcohol film obtained in step S1 is placed under a microneedle mechanical etcher for patterned etching, the microneedle size is 1 μm, and the etching speed is set to 1 μm / s. Then, a drop of cobalt ion photosensitive resin is dropped on the above-mentioned etching area, and a femtosecond laser direct writing technology is used to process a 3D micro-nano polymer structure with the etching area as the center, and the area ratio of the etching area to the bottom of the 3D micro-nano polymer structure is 1:50.

[0089] S3. Place the sample obtained in step S2 in an oven at 80° C. for 10 hours for stiffness strengthening treatment, then take out the sample and soak it in deionized water for 2 hours.

[0090] S4. The sample obtained in step S3 is pyrolyzed and calcined at 800° C. for 6 h in an oxygen atmosphere to obtain a distortion-free, high-quality cobalt oxide 3D micro-nano structure.

[0091] Example 5

[0092] Polypropylene alcohol is used as a strong polar polymer material and deionized water is used as a strong polar solvent. The strong polar polymer film is etched using femtosecond laser etching technology, and a weakly polar copper metal ion gel composite (the preparation method of the raw material is the same as that of the literature Nanomicro Lett, 2023, 15(1): 180.) is used to process the 3D micro-nano structure. The specific steps are as follows:

[0093] S1. Take 500 mg of polypropylene alcohol with a molecular weight of 2050 and mix it with 10 g of deionized water and stir it magnetically for 6 hours to obtain a colorless and transparent polypropylene alcohol solution. Fix the soda-lime glass substrate on the spin coater, take 300 μL of colorless and transparent polypropylene alcohol solution and evenly drop it on the substrate, then set the pre-spin coating parameters (speed of 500 rps, time of 10 s) and spin coating parameters (speed of 1500 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a 60°C hot plate and heat bake for 60 seconds to obtain a soda-lime glass substrate with a 0.4 μm polypropylene alcohol film spin-coated.

[0094] S2. Place the soda-lime glass substrate with the polyacryl alcohol film spin-coated in step S1 under a femtosecond laser etching system for patterned etching, with the etching parameters set to 10 mm / s and 45 mW. Then, inkjet printing technology is used on the above-mentioned etched area to process the copper ion gel composite 3D micro-nano structure with the etched area as the center, and the area ratio of the etched area to the bottom of the 3D micro-nano polymer structure is 1:25.

[0095] S3. Place the sample obtained in step S2 in an oven at 80° C. and heat-dry for 10 hours to strengthen the stiffness. Then take out the sample and immerse it in a deionized water solvent for 2 hours.

[0096] S4. Pyrolyze and calcine the sample obtained in step S3 at 500° C. for 6 h in an oxygen atmosphere, and then calcine at 1000° C. for 10 h in a hydrogen atmosphere to obtain a distortion-free, high-quality copper 3D micro-nano structure.

[0097] Example 6

[0098] Using polybutadiene as a non-polar polymer material and n-heptane as a non-polar solvent, femtosecond laser etching technology is used to etch the non-polar polymer film, and a weakly polar aluminum metal ion gel composite (the raw material preparation method is the same as the literature Nanomicro Lett, 2023, 15(1): 180.) is used to process the 3D micro-nano structure. The specific steps are as follows:

[0099] S1. Take 500 mg of polybutadiene with a molecular weight of 200,000 and mix it with 10 g of n-heptane and stir it magnetically for 6 hours to obtain a colorless and transparent polybutadiene solution. Fix the soda-lime glass substrate on the spin coater, take 300 μL of colorless and transparent polybutadiene solution and drip it evenly on the substrate, then set the pre-spin coating parameters (rotation speed of 500 rps, time of 10 s) and spin coating parameters (rotation speed of 1500 rps, time of 60 s), and start spin coating; place the spin-coated substrate on a 60°C hot plate and heat bake for 60 seconds to obtain a soda-lime glass substrate with a 0.5 μm polybutadiene film spin-coated.

[0100] S2. Place the soda-lime glass substrate with the polybutadiene film spin-coated in step S1 under a femtosecond laser etching system for patterned etching, with the etching parameters set to 10 mm / s and 45 mW. Then, an aerosol printing technique is used on the etched area to process the aluminum ion gel polymer 3D micro-nano structure with the etched area as the center, and the area ratio of the etched area to the bottom of the 3D micro-nano polymer structure is 1:30.

[0101] S3. Place the sample obtained in step S2 in an oven at 80° C. for 10 hours for stiffness strengthening treatment, then take out the sample and immerse it in n-heptane solvent for 2 hours.

[0102] S4. Pyrolyze and calcine the sample obtained in step S3 at 1200° C. for 8 hours in an oxygen atmosphere to obtain a 3D micro-nanostructure of aluminum oxide with no distortion and high morphological quality.

[0103] Comparative Example 1

[0104] The 3D micro-nano structure is processed using zinc ion photosensitive resin (same as in Example 1), and the specific steps are as follows:

[0105] S1. Drop a drop of zinc ion photosensitive resin on a soda-lime glass substrate, and use femtosecond laser direct writing technology to process a 3D micro-nano polymer structure on the substrate. The image of the 3D micro-nano polymer structure is shown in Figure 5 As shown, Figure 5Content a is a Primitive 3D structure. Figure 5 Content b is a partial enlarged view of the Primitive 3D structure. Figure 5 Content c is Diamond 3D structure, Figure 5 Content d is a partial enlarged image of the Diamond 3D structure. It can be seen that the 3D micro-nano polymer structure is in complete contact with the substrate.

[0106] S2, the sample obtained in step S1 was pyrolyzed and calcined at 600°C for 10 h in an oxygen atmosphere to obtain a zinc oxide 3D micro-nano structure as shown in FIG. Figure 6 As shown, Figure 6 Content a is a Primitive 3D structure. Figure 6 Content b is a partial enlarged view of the Primitive 3D structure. Figure 6 Content c is Diamond 3D structure, Figure 6 Content d is a partial enlarged view of the Diamond 3D structure. Figure 5 , Figure 6 It can be seen that the zinc oxide 3D micro-nano structure has serious morphological distortion and poor morphological quality. The reason is that the zinc oxide 3D micro-nano structure is adhered to the substrate. During annealing and shrinkage, the zinc oxide 3D micro-nano structure is stretched and deformed by the substrate, resulting in serious morphological distortion.

[0107] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for isotropic shrinkage of a three-dimensional micro-nano structure, characterized in that: The steps include: S1, spin coating a polymer solution on a substrate, and then heat-baking to obtain a polymer film; the polymer solution is formed by uniformly mixing a polymer material and a solvent, and the polymer material is one or more organic polymers with a molecular weight ≥ 1000; The polymer material is selected from at least one of polyethylene glycol, polypropylene glycol, polybutylene glycol, polyvinyl chloride, polystyrene, polyisobutylene, polyvinyl alcohol, polypropylene alcohol, polychloroprene vinylidene chloride-vinyl chloride copolymer, vinylidene chloride-vinyl chloride copolymer, polychloroprene and polybutadiene; S2, etching the polymer film to expose a portion of the substrate surface, taking the etched area as the starting processing position, processing the raw material of the three-dimensional structure into a target three-dimensional structure, so that the target three-dimensional structure is located at the bottom of the etched area and contacts the substrate surface, while the bottom of other parts contacts the unetched polymer film surface, wherein the area ratio of the etched area to the bottom of the target three-dimensional structure is 1:(2-100); The polymer film and the raw materials of the three-dimensional structure have different polarities, so that they are incompatible; S3, performing a stiffness strengthening treatment on the target three-dimensional structure, and then immersing it in the solvent to dissolve the unetched polymer film to obtain a three-dimensional micro-nano polymer structure; S4, thermally calcining the three-dimensional micro-nano polymer structure to obtain an isotropically shrunk three-dimensional micro-nano structure.

2. The method according to claim 1, characterized in that: In step S1, the mass ratio of the polymer material to the solvent is (0.01-0.5):

1.

3. The method according to claim 1, characterized in that In step S1, the substrate is selected from at least one of soda-lime glass, a silicon wafer and a silicon dioxide wafer.

4. The method according to claim 1, characterized in that In step S1, the heat-baking temperature is 50°C to 150°C, and the heat-baking time is 30s to 300s.

5. The method according to claim 1, characterized in that In step S2, the etching is selected from at least one of laser etching, mask etching, plasma etching and mechanical etching.

6. The method according to claim 1, characterized in that In step S3, the stiffness strengthening treatment is performed by at least one of ultraviolet irradiation and thermal baking; The heat drying temperature is 50°C to 200°C, and the time is 2h to 12h; The soaking time is 1h~6h.

7. The method according to claim 1, characterized in that In step S4, the pyrolysis calcination atmosphere includes at least one of air, oxygen, hydrogen and argon, the pyrolysis calcination temperature is 400° C. to 1200° C., and the pyrolysis calcination time is 5 h to 16 h.

8. An isotropically shrinkable three-dimensional micro-nano structure prepared according to the method according to any one of claims 1 to 7.

9. A product comprising the isotropically shrinkable three-dimensional micro-nano structure according to claim 8.

Citation Information

Patent Citations

  • Photoresist material for micro-nano processing as well as preparation and application thereof

    CN112947002A

  • Micronano array structure, fabrication method thereof and preparation of mask array for micronano array structure

    CN106444271A

  • Preparation method of metal and metal compound three-dimensional micro-nano structure

    CN115555578A